Agroindústria familiar e alimentação escolar: desafios para agregar valor e comercializar - Gonçalves, Polyanna Alves (2023)
The National School Feeding Program (PNAE) prioritizes the acquisition of foodstuffs produced locally and by family farming. However, despite the legal incentive and the release of resources, there are obstacles, both for family farmers and for public managers, to carry out public purchases of school feeding, especially in relation to processed foods. The following question then arises: what are the minimum requirements for the implementation of food processing units produced by family farming to offer institutional purchase of school feeding, in the scenario of Uberlândia-MG? This research aims to analyze the sanitary requirements for the production and sale of feeding by family farming for meal in municipal schools in Uberlândia-MG. The work has a qualitative approach and is presents itself as research-action. A documental analysis of the relevant legislation and regulations was carried out, especially with regard to the changes that have been taking place due to the incorporation of the concept of Economic Freedom. The advisory services provided by Cieps/PROEXC/UFU (Center for Incubation of Popular and Solidarity Enterprises of the Federal University of Uberlândia) to incubated family farmers is also presented, identifying the technical and social contributions. To analyze the results, a survey of purchases for school feeding in the municipal network was made, interview with representatives of the incubated farmers and a classification of the processing activities carried out in accordance with current regulations. It is concluded that the absence of financial resources for the implementation of an adequate agroindustry is the first difficulty for regularization and later sale for the public administration, and some doubts about what must be attended to for the regular implementation of the processing of foodstuffs by the family farming in Uberlândia-MG is a complicating factor for farmers. In addition, the need for continued incubation by Cieps/PROEXC/UFU of family farmers is pointed out, to help them keep up with the bureaucratic scenario, and also for the qualification of professionals involved in all stages of school feeding. As technological products of this research, a proposal for a course plan was presented for farmers to appropriate knowledge about legal aspects for the regularization of family agroindustries, in addition to a study of the physical-functional structure with environments, layout and adequate flows for the processing of foodstuffs in the context of family farming. Adapting production processes, minimizing supply difficulties for public purchases, adding value and expanding sales are essential strategic steps to deepen the generation of work and income in agrarian reform settlements.